Clinical diagnosis of femoroacetabular impingement. - Nepple, J; Prather, H; Trousdale, RT; Clohisy, J; Beaulé, P; Glyn-Jones, S; Kim, Y (2013)
The diagnosis of femoroacetabular impingement (FAI) syndrome is made based on a combination of clinical symptoms, physical examination findings, and imaging studies. A detailed assessment of each of these components is important to differentiate FAI from other intra- and extra-articular hip disorders. Clinical and physical examination findings must be viewed collectively because no single pathognomonic finding exists for FAI. Nevertheless, common components of the history and physical examination do suggest a diagnosis of FAI.